Adsorption of Lead Content in Leachate of Sukawinatan Landfill Using Solid Waste of Tofu - Sri Hartati; Dedik Budianta; Hermansyah Hermansyah (Sriwijaya Journal of Environment, 2016)
Abstract: A study on the adsorption of lead content in the leachate from the landfill by using solid waste of tofu. This study assed the effects of weight of the solid waste of tofu and the contact time on the efficiency of the Pb adsorption. The sample used in this study was artificial sample of a solution of Pb metal ion and the sample of the leachate of the landfill waste.  The study was carried out with a batch system, with the variables of weight of waste of tofu of 0.5; 1.0; 1.5 g. While the variables of the contact time were 0, 30, 60, 90, 120 and 150 minutes. To determine the optimum conditions, the waste of tofu was dissolved in 50 mL of Pb metal ion solution with a concentration of 20.27 mg/L and stirred with a shaker for 30 minutes at a speed of 180 rpm. The same thing was done by varying the contact time. When the optimum condition was obtained, it was applied with varying concentrations of Pb metal ion solution and garbage landfill leachate. The initial and the final levels of the Pb metal ion solution were analyzed by using the Atomic Adsorption Spectroscopy (AAS). The initial and the final results of the heavy metals were analyzed for disclosing the adsorption efficiency. To reveal the effects of the weight of the waste of tofu and the contact time, the data were analyzed with graphs. The waste of tofu with a weight of 1.5 g and a contact time of 90 minutes, had an adsorption efficiency of 97.68% at a concentration of 20.27 mg / L for Pb ion solution and 28.57% for the leachate from the landfill waste in 100 mL of leachate.Keywords: solid waste of tofu, adsorbent, adsorption, lead, leachate Abstrak (Indonesian): Telah dilakukan penelitian tentang adsorpsi kadar timbal dalam lindi dari sampah TPA dengan menggunakan limbah padat tahu. Penelitian ini akan mengkaji pengaruh berat ampas tahu dan waktu kontak terhadap efisiensi adsorpsi Pb. Sampel yang digunakan dalam penelitian ini adalah sampel buatan dari larutan ion logam Pb dan sampel dari lindi sampah TPA. Penelitian dilakukan dengan sistem batch, dengan variabel berat ampas tahu 0,5; 1,0; 1,5 g. Sedangkan variabel waktu kontak adalah 0, 30, 60, 90, 120 dan 150 menit. Untuk menentukan kondisi optimum, variabel berat ampas tahu dilarutkan dalam 50 ml larutan ion logam Pb dengan konsentrasi 20,27 mg/L lalu di aduk dengan shaker selama 30 menit dengan kecepatan 180 rpm. Hal yang sama dilakukan dengan variasi waktu kontak, setelah diperoleh kondisi optimum diaplikasikan dengan variasi konsentrasi larutan ion Pb dan lindi sampah TPA. Kadar larutan ion logam Pb awal dan akhir dianalisis dengan menggunakan Spektrofotometer Serapan Atom. Hasil awal dan akhir logam berat dianalisis untuk diketahui efisiensi adsorpsinya. Untuk mengetahui pengaruh berat ampas tahu dan waktu kontak data dianalisis dengan grafik. Ampas tahu dengan berat 1,5 g dan waktu kontak 90 menit, efisiensi adsorpsinya sebesar 97,68% pada konsentrasi 20,27 mg/L untuk larutan ion Pb dan 28,57% untuk lindi dari sampah TPA dalam 100 mL lindi.Kata kunci : limbah padat tahu, adsorben, adsorpsi, timbal, lindi.